PENGARUH DANA ALOKASI UMUM (DAU) DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP BELANJA DAERAH PADA KABUPATEN/KOTA DI PROVINSI SUMATERA BARAT - Jolianis, Jolianis (STKIP PGRI Sumatera Barat, 2014)
This study is to demonstrate empirically: 1) The effect of the General Allocation Fund to Expenditure. 2) The effect of local revenue against Expenditure. This study found that: 1) General Allocation Fund a significant effect on local spending. Increasing the amount of General Fund allocation will result in an increase in the number of Expenditure to be incurred by the local government. 2) the original income significantly influence the shopping area. Increasing the amount of the original income will result in an increase in the number of Expenditure to be incurred by the local government